Pengaruh Latihan Passing ke Dinding terhadap Kemampuan Passing Atas Bola Voli pada Ekstrakurikuler MTs Negeri 4 Kebumen Tahun Ajaran 2024/2025: Penelitian - Puput Widodo; Arfi Hasan; Arwan Adik Priyanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
MTs Negeri 4 Kebumen, which has an active volleyball extracurricular program, the results of observations show that basic skills such as overhead passing still need to be improved. This study aims to measure the effect of drill passing exercises with wall media on the overhead passing ability of students participating in extracurricular activities. This study uses a "one group pretest-posttest" design by measuring passing skills before and after treatment in different groups. The population in this study were 40 students who were active in the MTs Negeri 4 Kebumen extracurricular volleyball team who met the research criteria. The sample selection in this study used a purposive sampling technique. The sample used by the researcher in this study consisted of 20 students. Data analysis began with a normality test using Shapiro-Wilk to ensure that the pre-test and post-test data were normally distributed. Then, the homogeneity test of variance was carried out using the Levene test to ensure that the data variance was consistent, which is important for the validity of the t-test to be applied. Furthermore, paired sample t-test was used to evaluate the significant difference between the mean values ​​of pre-test and post-test, with a significance level of 5% (p < 0.05).